Slip effect on stagnation point flow and heat transfer over a shrinking/stretching sheet in a porous medium with suction/injection - Japili, Nirwana; Rosali, Haliza; Bachok, Norfifah (Akademia Baru Publishing, 2022)
The effects of thermal and velocity slip on Newtonian fluid steady boundary layer stagnation-point flow and heat transfer through a porous shrinking sheet with suction effect are investigated in the present research. By using a similarity transformation, the partial differential equation (PDE) is converted to an ordinary differential equation (ODE) and solved using the shooting technique to get numerical results. The flow characteristics for various values of the physical parameters are discussed, taking into consideration the effects of suction/injection as well as velocity and thermal slip. The local Nusselt number and skin friction coefficient, as well as the temperature and the velocity profiles, are presented as results. It is noticed that when the suction and velocity slip increase, the skin friction coefficient and local Nusselt number rise, as does the range of solutions that exist.